Safety, potential biotechnological and probiotic properties of bacteriocinogenic Enterococcus lactis strains isolated from raw shrimps. (April 2018) - Ben Braïek, Olfa; Morandi, Stefano; Cremonesi, Paola; Smaoui, Slim; Hani, Khaled; Ghrairi, Taoufik
Abstract: The aims of this study are to isolate new bacteriocinogenic lactic acid bacterial strains from white ( Penaeus vannamei ) and pink ( Palaemon serratus ) raw shrimps and evaluate their technological and probiotic potentialities. Seven strains were selected, among fifty active isolates, as producing interesting antimicrobial activity. Identified as Enterococcus lactis, these isolates were able to produce enterocins A, B and/or P. The safety aspect, assessed by microbiological and molecular tests, demonstrated that the strains were susceptible to relevant antibiotics such as vancomycin, negative for haemolysin and gelatinase activities, and did not harbour virulence and antibiotic resistance genes. The assessment of potential probiotic and technological properties showed a low or no lipolytic activity, moderate milk-acidifying ability, high reducing power, proteolytic activity and tolerance to bile ( P  < 0.05) and good autoaggregation and coaggregation capacities. Two strains designated as CQ and C43 exhibiting high enzymatic activities and bile salt hydrolase activity were found to display high survival under simulated in vitro oral cavity and gastrointestinal tract conditions caused by presence of lysozyme, pepsin, pancreatin, bile salts and acidic pH. This study highlights safe Enterococcus lactis strains with great technological and probiotic potentials for future application as new starter, adjunct, protective or probiotic cultures in food industry. Highlights: 7 enterocin-producing Enterococcus lactis ( E. lactis ) were isolated from shrimps Phenotypic, genotypic and safety characterisations were assessed to the enterococci E. lactis showed activities against pathogenic and spoilage microbes E. lactis strains display interesting biotechnological and probiotic potentials E. lactis CQ and C43 were able to survive through gastrointestinal tract passage